Therapeutic Alternatives for Managing Hypersensitivity in Teeth Affected by Molar Incisor Hypomineralization in Children: A Scoping Review - Anugerah, Evelyn; Andisetyanto, Prima (Riviera Publishing, 2026)
Molar incisor hypomineralization (MIH) is a prevalent dental condition in children, affecting approximately 13-14% of the pediatric population worldwide. Dental care for MIH poses significant challenges due to the abnormal morphology and structure of enamel prisms, resulting in increased porosity and fragility, which make the teeth highly susceptible to hypersensitivity. Managing dentin hypersensitivity (DH) in children with MIH is particularly difficult. This article reviews current evidence on various treatments for hypersensitivity in children with MIH-affected teeth to identify the most effective and long-lasting options. This scoping review adhered to the criteria established by the PRISMA-ScR and conducted a thorough literature search from 2019 to 2024 using the PubMed, Scopus, and Science Direct databases. The search utilized the Concept, Population, and Context framework along with specific keywords to identify therapies for hypersensitivity in children's teeth affected by MIH. Nine studies from Brazil, Italy, Austria, Germany, and China were included, involving children aged 6 to 16 years, with sample sizes ranging from 42 to 214 teeth. The studies examined the efficacy and long-term durability of different methods and materials while looking at a variety of management and treatment options for hypersensitivity in teeth affected by MIH. Treatments such as preemptive analgesia, sealants, laser therapy, and biomimetic hydroxyapatite paste effectively reduce hypersensitivity and improve quality of life related to oral health in children with MIH. The combination of laser therapy with desensitizers offers the most effective and sustained relief for hypersensitivity in MIH-affected teeth.